![](https://id-static.z-dn.net/files/d0a/51f00d88696baa06c775596916d23af0.jpg)
Jawaban:
1) - 48x³
2) 4x - 6
3) 8x + 4
4) - 216x² + 80x + 36
5) (14x² - 70x + 16)/(4x² - 20x + 25)
6) 96x² - 48x + 72
7) 26x - 5
8) (54x² - 24x + 45)/(81x² - 36x + 4)
Penjelasan dengan langkah-langkah:
1)
f'(x) = -(12)(4)x^(4-1) = - 48x³
2)
f(x) = 2x² - 3 - x - 5x = 2x² - 6x - 3
f'(x) = 4x - 6
3)
f(x) = 9x - 3x² - 5x + 6 + 7x²
f(x) = 4x² + 4x + 6
f'(x) = 8x + 4
4)
f(x) = (4 - 8x²)(7x + 2x - 5)
f(x) = (4 - 8x²)(9x - 5)
f(x) = 36x - 20 - 72x³ + 40x²
f(x) = - 72x³ + 40x² + 36x - 20
f'(x) = - 216x² + 80x + 36
5)
f(x) = [(8 - 7x²)/(5 - 2x)]
u = 8 - 7x²
u' = - 14x
v = 5 - 2x
v' = - 2
f'(x) = {[(- 14x)(5 - 2x) - (-2)(8 - 7x²)]/(5 - 2x)²}
f'(x) = [(- 70x + 28x² + 16 - 14x²)]/(25 - 10x - 10x + 4x²)
f'(x) = (14x² - 70x + 16)/(4x² - 20x + 25)
6)
f(x) = (6 - 8x)(-4x²-9)
f(x) = -24x² - 54 + 32x³ + 72x
f(x) = 32x³ - 24x² + 72x - 54
f'(x) = 96x² - 48x + 72
7)
f(x) = 19 - 20 + 13x² - 5x
f(x) = - 1 + 13x² - 5x
f(x) = 13x² - 5x - 1
f'(x) = 26x - 5
8)
f(x) = (- 5 + 6x²)/(9x - 2)
u = - 5 + 6x²
u' = 12x
v = 9x - 2
v' = 9
f'(x) = {[(12x)(9x - 2) - (9)(- 5 + 6x²)]/[(9x - 2)²]}
f'(x) = (108x² - 24x + 45 - 54x²)/(81x² - 18x - 18x + 4)
f'(x) = (54x² - 24x + 45)/(81x² - 36x + 4)
[answer.2.content]